Fabrication of somatosensitive actuators based on embbeded sensors and soft robotics grippers (2025)
This document presents the process of design. manufacturing, and testing of a sof robotic actuator with embbeded sensors with the purpose of using it as a part of a somatosensitive soft robotic gripper. To achieve this, an analytical model of the actuator, simulation procedures, and experimental testing was used to achieve the best parameters to guarantee the desired performance. All together with the use of 3D printing and fast curing elastomers as manufacturing methods, a prototype was developed integrated with a sensor circuit.